1971
DOI: 10.1161/01.str.2.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Hemiplegia

Abstract: Abstract:Osteoporosis in Hemiplegia • Localized osteoporosis in 25 long-term stroke patients was evaluated by means of measuring the combined cortical thickness in the humerus, radius and third metacarpal bones of both involved and noninvolved upper extremities. The combined cortical thickness was found to be consistently smaller on the involved side. Since the factors of weight bearing and calcium homeostasis were eliminated or controlled in this study, the authors were able to focus on the role of muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 16 publications
1
7
0
3
Order By: Relevance
“…Stroke patients fall mainly towards their paretic side due to balance problems and detoriation in neuromuscular response, which leads to a reduced ability to protect themselves when they fall [23][24][25]. Another contributing risk factor may be the development of disuse osteoporosis on the paretic side [1][2][3]8,9,11,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke patients fall mainly towards their paretic side due to balance problems and detoriation in neuromuscular response, which leads to a reduced ability to protect themselves when they fall [23][24][25]. Another contributing risk factor may be the development of disuse osteoporosis on the paretic side [1][2][3]8,9,11,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous cross-sectional studies have indicated that fractures are a common and serious complication after stroke [1][2][3][4] and they usually affect the paretic side. This might be caused by the high incidence of accidental falls in stroke patients [5][6][7] and by the development of osteoporosis, due to immobilization and other contributing factors [1,2,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Losses of cortical bone in man are seen in immobilization [1][2][3] and in senile osteoporosis [4,5]. Studies in our laboratory have also shown characteristic losses of tibial cortical bone in restrained hypodynamic monkeys [6].…”
Section: Methodsmentioning
confidence: 92%
“…At the same time excessive spasticity may cause fractures through uncontrolled limb movements, ie, in a wheelchair. Therefore, spasticity probably has two effects on bone: a low grade of spasticity benefits, while a high spasticity grade could be detrimental 21,22. Studies in spinal cord-injured (SCI) subjects have reported controversial results for the effect of spasticity on BMD, ie, either less reduction of BMD in the spastic SCI compared with flaccid SCI subjects, or spasticity may be protective against bone loss in SCI, but without any preserving effect in the tibia 23.…”
Section: Physiopathologic Mechanismsmentioning
confidence: 99%